Profil Évolutif Des Accidents Vasculaires Cérébraux Hémorragiques À Yaoundé (Hôpital Général& Centre Hospitalier Et Universitaire) - Awono Ateba, Patrice Emmanuel; Ndié, Justin; Likeng, Julienne Louise Ngo; Nkoum, Benjamin Alexandre (European Scientific Journal, ESJ, 2016)
Nowadays, strokes constitute a real public health problem in the world. In Cameroon, because of the people’s lifestyle potential risk factor, the prevalence of hemorrhagic strokes as well as its mortality is on the rise. This study was aimed at analyzing the evolutionary profile of hemorrhagic strokes at the General Hospital and the University Teaching Hospital in Yaoundé. A retrospective cross-sectional study with a qualitative component was carried out at the General Hospital and the University Teaching Hospital in Yaoundé for 2 months. Were included, all patients with a diagnosis of hemorrhagic strokes confirmed by CT Scan. With the help of a scale, patient data over a 30 month’s period (2013-2015) were collected. Over 1037 patients hospitalized in intensive care unit at the General Hospital and the University Teaching Hospital in Yaoundé, 122 cases of hemorrhagic strokes were diagnosed, that is a prevalence of 11.8%. The average age was 58±10.52 and the most vulnerable age range was between 50 and 70 years with 67.2%. Men were most affected (60.7%) with a sex ratio of 1.54(74 men/48 women). Among these cases of hemorrhagic strokes still hospitalized, 70 had died giving a lethality rate of 57.4%. Only the duration of hospitalization had an effect on the outcome of patients with hemorrhagic strokes. Actually the patients, victims of hemorrhagic strokes who had had less than 21 days of hospitalization, had 2.91 chances of dying as compared to those patients hospitalized for over 21 days (OR=2.91 IC 95% [5.1-65.7]; p=0.000). The late admission to reanimation, the difficulties encountered by victims of hemorrhagic strokes and their careers, to handle the enormous cost of their treatment and the insufficiencies of the technical platform, were factors also influencing the evolution of hemorrhagic strokes hospitalized in reanimation at the General Hospital and the University Teaching Hospital in Yaoundé. Despite certain efforts aimed at reducing premature mortality, the prevalence of hemorrhagic strokes was increasing in reanimation at the General Hospital and University Teaching Hospital in Yaoundé. Only multisectorial actions of sensitization, the restructuring and amelioration of the care of this ailment will help reverse the evolutionary trend.